Hystometric evaluation of nickel chronic exposure effects on large instestine of adult Wistar male rats - Assis-Rodrigues, Maria Luiza; Rodrigues-Sartori, Sirlene Souza; Santos-Totaro, Priscila Izabel; Pinto da Matta, Sérgio Luis (Revista de Ciencias Agrícolas, 2019)
The ingestion of considerable amounts of water or food contaminated with nickel can be very toxic. The present work was conducted aiming to evaluate the effects of nickel exposures on ascending colon of adult Wistar male rats at hystometric level. We used 12 animals that were divided in a control (ingested uncontaminated water) and a nickel-contaminated (i.e., 25 mg de nickel/L of water) groups. Nickel chloride was offered in declorinated water and the experiment had a 56 days exposure period. A portion of the ascending colon was removed of the animals and subjected to hystological labelling processes using blue toluidin (for general hystometric description), Alcian Blue (AB, for acid mucins) and periodic acid-Schiff (PAS) technique (for neutral mucins). The potential differences between groups were desgined by applying the Whitney test and t test (p < 0.05). The crypts were smaller for the nickel-contaminated group, even though these organism exhibited broader and higher crypts. Nickel-contaminated animals exhibited a smaller amount of calyceform cells with AB and PAS positive reactions as well as a less mucus quantities when compared with nickel-uncontaminated animals. Such reductions on the amount of calyceform cells with AB and PAS positive reactions may be related wiht the shallower crypts, which possibly reduced the synthesis and secretion of mucins, compromissing the functional aspects (e.g., lubrification and intestinal mucosa protection) of the nickel-contaminated large intestines. Interestingly, the wider and higher crypts and higher epithelium collumn on the nickel-contaminated animals may represent a relevant trade-off for the intestinal mucosa protection.